DAPHNE SLEIGH, The Man Who Saved Vancouver: Major James Skitt Matthews - Keirstead, Robin (Archivaria, 2010)
The Man Who Saved Vancouver: Major James Skitt Matthews. DAPHNE SLEIGH. Victoria: Heritage House, 2008. 240 p. ISBN 978-1-894974-39-4